The Influence of Air Pollution Around Main Arterial Roads on the Respiratory Symptoms of Schoolchildren - IWASAKI, Akiko; NITTA, Yoshio; TANAKA, Yoshiaki; ADACHI, Motoaki; SHIMA, Masayuki (Journal of Japan Society for Atmospheric Environment / Taiki Kankyo Gakkaishi, 1996)
In order to evaluate the effects of air pollution around main arterial roads with heavy traffic on the respiratory symptoms of schoolchildren, a cohort study was performed in primary schools in Chiba Prefecture. The schoolchildren were observed from 1992 through 1994. The prevalence and incidence of asthma were compared for three goups: subjects residing within 50 meters of the main arterial roads in urban areas; subjects residing over 50 meters from the roads in urban areas and subjects residing in rural areas. For all three years, the prevalence of asthma was highest in girls residing within 50 m from the roadsides, and the girls in rural areas had the least prevalence. In boys, this trend was found only in the second year. The incidence of asthma in the two-years period was 5.7% in boys residing within 50 m from the roadsides, 3.9% in boys residing over 50 m from the roads, and 1.6% in boys residing in the rural areas. The incidence of asthma in girls were 3.3%, 2.5%, and 1.0%, respectively. The multiple logistic regression analysis was perfomed to determine the adjusted odds ratios. In boys, the adjusted odds ratios for the incidence of asthma, relative to subjects in rural areas, were 3.70 in subjects residing within 50 m from the roadsides and 1.92 in subjects residing over 50 m from the roads. In girls, the odds ratios were 5.97 and 2.44, respectively. These findings suggest that air pollution around main arterial roads increases the incidence of asthma in schoolchildren.